Transition of dominant lattice sites of Mg in InN:Mg revealed by Raman scattering. (August 2018) - Chen, Zhaoying; Sui, Jingyang; Wang, Xinqiang; Kim, Kumsong; Wang, Ding; Wang, Ping; Wang, Tao; Rong, Xin; Harima, Hiroshi; Yoshikawa, Akihiko; Ge, Weikun; Shen, Bo
Abstract: The behavior of Mg dopants in InN films grown by molecular beam epitaxy was studied by Raman scattering in a wide Mg concentration ([Mg]) range from 1 × 10 16 to 4 × 10 21  cm −3 . Transition of dominant lattice sites of Mg dopants was investigated through a diffusion-collision model based on Mg-related local vibrational modes, which was further confirmed through stress analysis. It was found that Mgi and MgIn -N-Ini are the dominant sites of Mg dopants at [Mg] < 1.8 × 10 20  cm −3, while the complex of MgIn -N-Mgi dominates with further increasing [Mg]. This study provides an insight on the behavior of Mg and would be helpful for achieving effective p-type doping in InN. Highlights: Transition of dominant lattice sites of Mg dopants was revealed by Raman scattering with a diffusion-collision model. Stress induced by Mg doping was perfectly explained by lattice distortion around Mg dopants and growth mode transformation. The Mg concentration at the transition point indicates a critical concentration for effective p-type doping of InN. Raman scattering of LVMs is helpful for understanding the doping behavior of Mg and achieving effective p-type doping of InN.